CASE ANALYSIS OF AR-RAHN ACCEPTANCE AND ACCOUNTING TREATMENT ACCORDING TO SFAS 107 CASE STUDY OF WEST JAVA BANK SYARIAH TANGERANG BRANCH - Srie Nuning Mulatsih; Nela Dharmayanti; Budiastuti Fatkar (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2018)
This research aims to know the implementation of accounting gold investment product at Bank Jawa Barat Syariah brand Tangerang. That BJB Syariah murabahah and rahn based on PSAK107. This research is descriptive qualitative research, a method that is done is to interpret and said data concerned with the current situation, attitudes and opinion that accur in the relationship between the variable, the different between fact, the effect of the condition, and others. Data processing method using interviews and accompanied with documents related the research. The result showed that the accounting treatment that the recognition, measurement, presentation recognition of Bank BJB Syariah ar-rahn are inaccordance with PSAK 107.